Fremde Richter Die Rechtsprechung im Fürstentum Liechtenstein unter dem Einfluss schweizerischer und deutsch-österreichischer Richter 1938-1945 - Perrez, Anna-Carolina (Chronos Verlag, 2015)
Foreign judges The Influence of Swiss and German-Austrian judges upon jurisprudence in the principality of Liechtenstein, 1939-45 The principality of Liechtenstein has been a small country possessing limited resources. In matters of jurisprudence this meant adopting Austrian and Swiss legal codes and, along with local lawyers, electing attorneys from both neighboring countries as judges in Liechtenstein. While this practice worked during times of peace, it became tenuous during the era of National Socialism, and connected to the problem of potential national socialist influence upon the appointment of judges and on the practice of law. The annexation of Austria by the "Third Reich" turned Austrian judges working in Liechtenstein into "German" judges, who dispensed justice according to Nazi law in their home-land, but according to Liechtenstein law within the principality. Can a political influence upon these judges be shown? Did a national socialist spirit pervade Liechtenstein jurisprudence and the laws enacted during that time? What was the stance taken by the judges who were Swiss? The author discusses the peculiarities of justice in Liechtenstein during the Second World War.